Molecular mechanisms of silybin and 2,3-dehydrosilybin antiradical activity--role of individual hydroxyl groups - Gazák, Radek; Sedmera, Petr; Vrbacký, Marek; Vostálová, Jitka; Drahota, Zdenĕk; Marhol, Petr; Walterová, Daniela; Kren, Vladimír (Free radical biology & medicine, 2009)
The flavonolignans silybin (1) and 2,3-dehydrosilybin (2) are important natural compounds with multiple biological activities operating at various cell levels. Many of these effects are connected with their radical-scavenging activities. The molecular mechanisms of the antioxidant activity of these compounds and even the functional groups responsible for this activity are not yet well known. Their mechanism can be inferred from the structures of the dimeric products obtained from radical-mediated reactions of selectively methylated derivatives of 1 and 2. The radical oxidation of 1 methylated at 7-OH and 2 methylated at both 3-OH and 7-OH yields C-C and C-O dimers that enable the molecular mechanism of their E-ring interaction with radicals to be elucidated and shows the importance of the 20-OH group in this respect. The pivotal role of the 3-OH group in the radical-scavenging activity of 2 was confirmed through the formation of another type of dimer from its selectively methylated derivative.
Keywords: Silymarin; oxidační stres; hydroxylový radikál; silibinin; Hydroxyl Radical; techniky in vitro; ostropestřec mariánský; silymarin; Silybin; molekulární modely; oxidace-redukce; Models, Molecular; dimerizace; Free Radical Scavengers; peroxidace lipidů; Dimerization; Lipid Peroxidation; Oxidation-Reduction; Oxidative Stress; Silybum marianum; scavengery volných radikálů; In Vitro Techniques